Peranan Pojok Baca dalam Menumbuhkan Minat Baca Siswa Sekolah Dasar - Agung Rimba Kurniawan; Destrinelli Destrinelli; Suci Hayati; Rahmad Rahmad; Juwi Riskayanti; Intan Sefti Wasena; Yanuar Triyadi (Universitas Negeri Padang, 2019)
The purpose of this study is to describe the role of the reading corner in fostering students' interest in reading in elementary school. This type of research is phenomenology with a qualitative approach. The informants of this study were the homeroom teacher 1,2,3,4,5, and 6 primary schools 34/1 Lotus, the data collection instrument used observation sheets, interviews, and documentation. The results of this study are seen that the reading corner has a very important role in fostering students' interest in reading in elementary school, this is evident from the presence of several reading corner roles that can foster interest in reading students in elementary school. This study can be concluded that the reading corner is very helpful in fostering students 'interest in reading in the classroom, the role of the reading corner in growing students' interest in reading is, as a facilitator where to read, as the closest reading material, a comfortable reading place and an interesting reading place, so that of some the role helps foster students' interest in reading in elementary school.